Physical effort exertion and pain: Links with trait-based risk for psychopathology. (January 2019) - Abplanalp, Samuel J.; Fulford, Daniel
Highlights: Schizotypy and anhedonic depression were positively associated with pain following a physical endurance/effort task. These results hold true after accounting for age, sex, task performance, average hours of exercise per week, and baseline pain. Hypomania was not associated with pain following a physical endurance/effort task. Abstract: People with serious mental illness (SMI) are at an increased risk for physical health complications, such as cardiovascular disease and obesity. Low levels of physical activity is a major contributor to these health complications. One factor associated with limited physical activity in the broader sedentary population is pain. While preliminary findings suggest an association between lack of physical activity and pain in SMI, conclusions are still unclear. Thus, the goal of this correlational study was to examine associations between trait-based risk for psychopathology (hypomanic personality, schizotypy, and anhedonic depression) and the experience of pain following a physical endurance/effort task. Healthy participants (N = 43; 18 females) completed self-report measures of trait-based risk for psychopathology. They also reported on the experience of pain before and after the Time To Exhaustion (TTE) test. Findings revealed that risk for psychosis and anhedonic depression were associated with increases in pain following the TTE test, accounting for other key variables, such as age and self-reported physical exercise. Risk for mania was unrelated to changes in pain. These results suggest that the experience of pain in relation to physical endurance/effort may contribute to diminished physical activity among people at risk for SMI.